Pengaruh Ukuran Perusahaan, Likuiditas, dan Perataan Laba Terhadap Kualitas Laba - Fifi Devi Yoanita; Khairunnisa Khairunnisa (Universitas Katolik Soegijapranata Semarang, 2021)
Earnings is a component of financial statements that describes the level of profitability of a company. The earning information listed on the financial statements should be of quality because investors can use profits to assess the company's future performance. This research aims to determine the influence of company size, liquidity, and income smoothing on earning quality in transportation sub-sector companies listed on the Indonesia Stock Exchange for the period 2015-2019. To collect samples, this study uses purposive sampling which result in 45 firm observations. The data analysis technique used is multiple linear regression analysis. The results showed that company's size, liquidity, and income smoothing have significant positive effects on earning quality. In particular, the size of the company and income smoothing partially have significant positive effects on earning quality. Meanwhile, liquidity has no effect on earning quality.